The hero with a thousand faces. - Campbell, Joseph (Bollingen series., 2008)
Since its release in 1949, The Hero With a Thousand Faces has influenced millions of readers by combining the insights of modern psychology with Joseph Campbells' revolutionary understanding of comparative mythology. In these pages, Campbell outlines the Hero's Journey, a universal motif of adventure and transformation that runs through virtually all of the world's mythic traditions. He also explores the Cosmogonic Cycle, the mythic pattern of world creation and destruction.